Glypican-1 nanoliposomes for potentiating growth factor activity in therapeutic angiogenesis. (July 2016) - Monteforte, Anthony J.; Lam, Brian; Das, Subhamoy; Mukhopadhyay, Somshuvra; Wright, Catherine S.; Martin, Patricia E.; Dunn, Andrew K.; Baker, Aaron B.
Abstract: Therapeutic angiogenesis is a highly appealing concept for treating tissues that become ischemic due to vascular disease. A major barrier to the clinical translation of angiogenic therapies is that the patients that are in the greatest need of these treatments often have long term disease states and co-morbidities, such as diabetes and obesity, that make them resistant to angiogenic stimuli. In this study, we identified that human patients with type 2 diabetes have reduced levels of glypican-1 in the blood vessels of their skin. The lack of this key co-receptor in the tissue may make the application of exogenous angiogenic growth factors or cell therapies ineffective. We created a novel therapeutic enhancer for growth factor activity consisting of glypican-1 delivered in a nanoliposomal carrier (a "glypisome"). Here, we demonstrate that glypisomes enhance FGF-2 mediated endothelial cell proliferation, migration and tube formation. In addition, glypisomes enhance FGF-2 trafficking by increasing both uptake and endosomal processing. We encapsulated FGF-2 or FGF-2 with glypisomes in alginate beads and used these to deliver localized growth factor therapy in a murine hind limb ischemia model. Co-delivery of glypisomes with FGF-2 markedly increased the recovery of perfusion and vessel formation in ischemic hind limbs of wild type and diabetic mice in comparison to mice treated with FGF-2 alone. Together, our findings support that glypisomes are effective means for enhancing growth factor activity and may improve the response to local angiogenic growth factor therapies for ischemia.